Some Thoughts on Practical Stabilization Policy - Eichenbaum, Martin (American Economic Review, 1997)
This paper argues that the primary objective of monetary policy should be long run price stability or at least a low average rate of in°ation. But there is also a welfare improving role for monetary policy in helping the economy adjust to nonpolicy shocks. This gives rise to a fundamental tension in the conduct of monetary policy. Understanding this tension is central to interpreting the qualitative properties of actual monetary policy, for evaluating its e®ects and for thinking about alternative institutions that would lead to better monetary policy. Is there a core of practical macroeconomics that we should all believe? 1 Given my limited space constraints, I won't try to discuss a top ten list of eternal macro truths. Nor will I discuss the importance of modelling macro phenomena using quantitative general equilibrium models. Instead I will approach the question from the perspective of stabilization policy. So de¯ned, my answer to the question is: Yes, there is a core of practical macro. And as regards stabilization policy, most of it has been learned in the past twenty eight years as